"Fourth Generation" Universities and Regional Development - Bence Zuti; Miklós Lukovics (Stünings Medien, 2015)
Nowadays the competitiveness of regions is affected and altered by globalization and other background processes that serve as arrangers of regional structure and for this reason they deserve attention. In the global competition, immaterial assets like knowledge or social capi-tal become key aspects, and engines of economic development. In regional studies, knowledge is dentified as a crucial factor of re-gional development. Knowledge became the main asset of pro-duction, it is considered as a new engine of economic development, hereby the role of knowledge, innovation, technology and learning is necessary to be reconsidered. This can also be derived by the fact that the presence of innovation fundamentally determines the com-petitiveness of regions and continuous innovation is required to ob-tain competitive edge (Lengyel 2000). We can point out that the competitive edge of developed economies mainly relies on their abil-ity to create and utilize knowledge (Grosz - Rechnitzer 2005).
Keywords: I20; I23; I25; R10; 330; "Fourth Generation" Universities; Regional Development; Higher education